Current issues of the Russian language teaching XIV - Dohnal, Josef (Sborník prací Pedagogické fakulty Masarykovy univerzity, 2020)
Collection of papers "Current issues of the Russian language teaching XIV" is devoted to issues of methodology of teaching Russian as a foreign language, to issues of linguistics and literary science and includes papers related to the use of online tools and resources in teaching Russian. This collection of papers is a result of the international scientific conference "Current issues of the Russian language teaching XIV", which was scheduled for 8-10 May 2020, but due to the pandemic COVID-19 took place remotely.